Decentralization and self-government in Russia, 1830-1870 - Starr, S. Frederick (Princeton, New Jersey : Princeton University Press, 1972)
The turbulent period of renewal and innovation that followed Russia's crushing defeat in the Crimea has been interpreted, historically, in terms of the emancipation of the serfs and the evolution of the gentry class. But, contends Frederick Starr, such an approach underestimates the breadth and intensity of the impulse for local reforms per se. After tracing the ideological sources of the reform, Mr. Starr examines in detail the legislative process by which administrative decentralization and public self-government were instituted.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Preface -- I. The Undergoverned Provinces, 1830-1855 -- II. The Ideology of Reform -- III. The Politics of Decentralization -- IV. The Politics of Self-Government -- V. New Reforms, Changed Conditions, Old Habits, 1864-1870 -- VI. Conclusions -- Selected Bibliography -- Index
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Decentralization in government -- Russia -- History; Local government -- Russia -- History; Administration locale -- Russie -- Histoire; Décentralisation administrative -- Russie -- Histoire; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Decentralization in government; Local government; Russia; Dezentralisation; Selbstverwaltung; Russland; History